2020
DOI: 10.1007/s12217-020-09828-6
|View full text |Cite
|
Sign up to set email alerts
|

Phase Separation in Porous Media Integrated Capillary Channels

Abstract: Phase separation in space is critical for gas-free propellant supply, life support systems, refueling of spacecraft in low earth orbit (LEO), and for deep space exploration missions. In the absence of gravity, the stability of the liquid-gas interface depends on capillary forces. High liquid flow rates, sudden accelerations, and vibrational disturbances can cause the free surface of the liquid to collapse, which results in the ingestion of gas. Propellant tanks may have screen channel liquid acquisition device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Многофазные течения через пористую среду рассматриваются во многих исследованиях. Течение жидкости и поведение границы раздела фаз в небольших каналах различной формы изучались на борту международной космической станции [9][10][11]. Движение пузырьковой структуры в условиях микрогравитации рассмотрено в [12].…”
Section: рис 2 капиллярная пропитка пористой среды со вставкойunclassified
See 1 more Smart Citation
“…Многофазные течения через пористую среду рассматриваются во многих исследованиях. Течение жидкости и поведение границы раздела фаз в небольших каналах различной формы изучались на борту международной космической станции [9][10][11]. Движение пузырьковой структуры в условиях микрогравитации рассмотрено в [12].…”
Section: рис 2 капиллярная пропитка пористой среды со вставкойunclassified
“…величину ξ конкретизируем впоследствии так, чтобы по возможности убрать «лишние» члены в уравнении неразрывности (7), которые появятся там после подстановки уравнений импульса. Заметим, что при выполнении (11) автоматически соблюдается (10), давления же фаз p α ниже заменим на комбинацию (p,ξ). Назовем эти значения средним давлением и поправкой к нему.…”
Section: математическая модель капиллярной пропитки с учетом гистерезисаunclassified
“…The knowledge of the geometry of the metallic screen is sufficient to calculate geometric properties such as the pore diameter, porosity, thickness of the screen, and surface-to-volume ratio using the proper equations [ 11 , 12 ]. Numerous experimental and simulated data can be found in the literature where metallic screens have been tested under Earth gravity conditions and in microgravity environments [ 13 , 14 , 15 , 16 , 17 ]. After two initial papers dealing with the applicability of porous SiOC monoliths for isothermal/cryogenic wicking [ 18 , 19 ], there are, to the authors’ knowledge, no data reported on the further development of these materials into crack-free SiOC as SC-LADs, the correlation of experimental results with the pore structure, or an analytical solution.…”
Section: Introductionmentioning
confidence: 99%
“…The liquid phase tends to attach on the walls and surround the gas phase, resulting in a mixture of gas and liquid at the outlet of the tank . Passive phase separation based on porous material, which takes full advantage of the capillary force, is an important technique in liquid management and advanced life support systems for spacecraft, including gas-free water acquisition from water tanks, orbital propellant acquisition devices, and gas port phase separators. For example, a screen channel liquid acquisition device (LAD) is a successful application of porous material in phase separation. Screen channel is a hollow duct composed of three walls and a porous wall made from metal wire mesh.…”
Section: Introductionmentioning
confidence: 99%